Radiocarbon and Calibration: Potential for Andean Archeology - León Canales, Elmo (2006)
This paper is mainly based on the handbook written by Dr. Taylor (198 7) on radiocarbon, which is still in force despite of the years. lt does not covers all the literature, but quotes sorne basic texts as references. The second part of the text, which is shorter and complementary to the first, is an exercise of calibration on a an eposide of andean archaeology, as a means to evaluare the importanc of examining past events on calendar years instead of radiocarbon ones. The final aim of this essay is to motivare students to apply calibration in their research, as well as in their thesis and monographic works, in arder to start evaluating our history on the basis of astral years and not only radiocarbon ones, which is currently the usual approach.